The Set2-RPB1 Interaction Domain of Human RECQ5 Is Important for Transcription-Associated Genome Stability - Li, Min (American Society for Microbiology, 2011)
The conserved RECQ5 DNA helicase is a tumor suppressor in mammalian cells. Defects in RECQ5 lead to the accumulation of spontaneous DNA double-stranded breaks (DSBs) during replication, despite the fact that these cells are proficient in DSB repair by homologous recombination (HR). The reason for this is unknown. Here, we demonstrate that these DSBs are linked to RNA polymerase II (RNAPII)-dependent transcription. In human RECQ5-depleted cells, active RNAPII accumulates on chromatin, and DNA breaks are associated with an RNAPII-dependent transcribed locus. Hence, transcription inhibition eliminates both active RNAPII and spontaneous DSB formation. In addition, the regulatory effect of RECQ5 on transcription and its interaction with RNAPII are enhanced in S-phase cells, supporting a role for RECQ5 in preventing transcription-associated DSBs during replication. Finally, we show that the SET2-RPB1 interaction (SRI) domain of human RECQ5 is important for suppressing spontaneous DSBs and the p53-dependent transcription stress response caused by the stalling of active RNAPII on DNA. Thus, our studies provide novel insights into a mechanism by which RECQ5 regulates the transcription machinery via its dynamic interaction with RNAPII, thereby preventing genome instability.